Organizações não governamentais - ONGs como espaço de investimento profissional - Oliveira Júnior, Carlos Augusto de (2006)
The Non-governmental organizations (NGOs) progressively expand and assume a relevant role in contemporary society. With NGOs expansion in Brazil and the rest of the world, also increases people interest to enter this universe, motivated by a strong sense of dedication to social causes, as well as to achieve personal and professional recognition through the exercise of a labor that could make sense to him or her. On the other hand, NGOs expansion brings some challenges, among them the adoption of managerial practices and procedures aiming to attract, develop and retain competent and dedicated professionals, in order to achieve effective results in its actions, especially in a context of intensive competition for financial resources. This study aims to investigate whether NGOs represent opportunity for professional investment, and was based on theoretical analysis of concepts such as people hiring, keeping and resigning, in the perspective of people employed with them and in NGOs own perspective, through a critical-reflexive approach of human management subsystems, eventually adopted. This is an explanatory and descriptive research, managed through a multiple case study, subsided by 12 (twelve) interviews and 19 (nineteen) questionnaires answered by managers and collaborators of 3 (three) most prominent NGO in Brazilian state of Ceará. Data were treated qualitatively employing quantitative instruments. The research allowed to evidence that surveyed organizations assign importance to human management, nevertheless not adopting structured practices in order to promote the collaborators permanence, discerning that hiring and permanence of them proceeds from the desire of professional qualification, of joining in these organizations an space of identification with the social causes that he/she protect and believe, and by the work environment (organizational climate) provided.